Socioeconomic determinants of mental health outcomes among Hawaii adults - Juarez, Ruben; Le, Binh; Bond-Smith, Daniela; Bonham, Carl; Sanchez-Johnsen, Lisa; Maunakea, Alika K. (Frontiers in Public Health, 2025)
BackgroundSocioeconomic factors play a critical role in influencing mental health outcomes, particularly during periods of crisis such as the COVID-19 pandemic. In Hawaiʻi, working adults face unique challenges related to employment, food security, and trust in community safety measures, which may exacerbate risks for depression, low self-esteem, and suicidal ideation. Understanding the interplay of these factors is crucial to addressing mental health disparities and informing targeted policy interventions.MethodsThis study analyzed data from 2,270 adults aged 18 to 65 residing in Hawaiʻi, collected in 2022. Using probit regression models and conditional inference decision trees, the study assessed the impact of 15 socioeconomic and demographic factors on mental health outcomes, specifically symptoms of depression, low self-esteem, and suicidal ideation. Key variables of interest included food security status, employment, marital status, pre-existing health conditions, and perceptions of COVID-19-related community safety.ResultsThe findings revealed significant mental health challenges among the participants, with 39.6% reporting symptoms of depression, 14.7% experiencing low self-esteem, and 4.2% expressing suicidal ideation. Food insecurity emerged as the most significant predictor of poor mental health, particularly for depression and suicidal ideation. Within the food-insecure group, individuals with pre-existing health conditions faced worsened mental health outcomes, while marital status served as a protective factor. Employment reduced the likelihood of depression by 2.8%, and perceptions of community safety during the COVID-19 pandemic were associated with a 9.9% reduction in depression risk.ConclusionFood insecurity, particularly when coupled with pre-existing health vulnerabilities, is a critical risk factor for adverse mental health outcomes among working adults in Hawaiʻi. Employment and positive perceptions of community safety were identified as key protective factors. These findings highlight the urgent need for targeted interventions to improve food security and foster community trust and safety.